2015
DOI: 10.1136/bmjopen-2014-006777
|View full text |Cite
|
Sign up to set email alerts
|

Is schizophrenia associated with an increased risk of chronic kidney disease? A nationwide matched-cohort study

Abstract: ObjectiveThe impact of schizophrenia on vital diseases, such as chronic kidney disease (CKD), has not as yet been verified. This study aims to establish whether there is an association between schizophrenia and CKD.DesignA nationwide matched cohort study.SettingTaiwan's National Health Insurance Research Database.ParticipantsA total of 2338 patients with schizophrenia, and 7014 controls without schizophrenia (1:3), matched cohort for sex, age group, geography, urbanisation and monthly income, between 1 January… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 36 publications
3
35
0
2
Order By: Relevance
“…23 , 24 However, there has been limited research investigating the prevalence of, and risk factors for, CKD in people with SMI. 13 , 25 , 26 In the UK, primary care plays an important role in the management of physical health conditions in people with SMI. As part of the Quality and Outcomes Framework (QOF), there have been recent financial incentives for general practitioners (GPs) to undertake physical health checks in people with SMI.…”
Section: Introductionmentioning
confidence: 99%
“…23 , 24 However, there has been limited research investigating the prevalence of, and risk factors for, CKD in people with SMI. 13 , 25 , 26 In the UK, primary care plays an important role in the management of physical health conditions in people with SMI. As part of the Quality and Outcomes Framework (QOF), there have been recent financial incentives for general practitioners (GPs) to undertake physical health checks in people with SMI.…”
Section: Introductionmentioning
confidence: 99%
“…Se postula que es la misma disfunción endotelial que predispone a los pacientes a desarrollar otras enfermedades como DM2 y HTA la que estaría causando la ERC, sin embargo, se necesita más investigación en el área. Se sugiere entonces buscar dirigidamente ERC en los pacientes con EQZ y manejar las comorbilidades para prevenirla 42 .…”
Section: Enfermedad Renal Crónicaunclassified
“…Moreover, recurrent evidence exists linking microtubules/cytoskeleton and SCZ [72][73][74][75][76][77][78]. There is not much evidence for kidney development and SCZ, but there have been studies showing that SCZ is associated with chronic kidney disease, even after controlling for demographic, behavioral, and medical risk factors [79,80]. Furthermore, a study found a polygenic signature differentiating SCZ from controls, which could also significantly differentiate type 2 diabetes patients from controls by predicting a glycemic control indicator, supporting a molecular commonality between SCZ and type 2 diabetes [81].…”
Section: Discussionmentioning
confidence: 99%